1964
DOI: 10.2136/sssaj1964.03615995002800050034x
|View full text |Cite
|
Sign up to set email alerts
|

Water Movement and Loss Under Frozen Soil Conditions

Abstract: Soil water and temperature distributions in a silty clay loam soil were studied in the field under freezing winter conditions. Appreciable upward water movement to a frozen zone occurred in plots in which the unfrozen subsoil water was held at tensions of less than about 2 atm. and water held at tensions of less than 5 atm. moved toward the frozen zone. It appears that the upward water movement to the frozen zone conributed to overwinter water losses since soil water losses of 0.36 and 0.50 inches were measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

1972
1972
2004
2004

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(16 citation statements)
references
References 0 publications
1
15
0
Order By: Relevance
“…2 and other reports of similar research (Sartz, 1969;Fergusen et al, 1964;and Benz et al, 1968). For example, the rate of upward water flux increases as the amount of soluble salt in the soil increases because the thicker unfrozen water films provide a greater hydraulic conductivity, The decreasing rate of upward movement with time (Fig, 2-A and 2-D) results from a decreasing water matric potential gradient (Fig.…”
Section: -Ras Kw-70d87ksupporting
confidence: 53%
See 2 more Smart Citations
“…2 and other reports of similar research (Sartz, 1969;Fergusen et al, 1964;and Benz et al, 1968). For example, the rate of upward water flux increases as the amount of soluble salt in the soil increases because the thicker unfrozen water films provide a greater hydraulic conductivity, The decreasing rate of upward movement with time (Fig, 2-A and 2-D) results from a decreasing water matric potential gradient (Fig.…”
Section: -Ras Kw-70d87ksupporting
confidence: 53%
“…In the fall, the soil is uniformly wet as shown by the dashed line. After freezing, the water would migrate toward the surface, and the curved line would approximate the water distribution just before thawing in the spring (Fergusen et al, 1964). Further suppose that the [Na]/(Ca -1--Mg] ratio in the fall, was such that the soil was just on the borderline of becoming a problem.…”
Section: Practical Aspectsmentioning
confidence: 99%
See 1 more Smart Citation
“…During the soil thaw, surface soil is often underlain with frozen subsoil which impedes drainage and creates water saturated conditions (Ferguson et al 1964;Startz 1969;Malhi 1978). Water saturation creates an anaerobic environment favoring reduction of NO 3 -by denitrifiers.…”
mentioning
confidence: 99%
“…These results indicated that N loss through leaching was minimal. According to several researchers (Ferguson et al 1964;Sartz 1969;Malhi 1978), the surface soil becomes saturated during the soil thaw in early spring because of impeded drainage caused by underlying frozen subsoil. Despite low soil temperatures, this saturated surface soil apparently creates anaerobic conditions which enhance denitrification activity.…”
Section: Discussionmentioning
confidence: 99%